The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1007/s10479-023-05266-w
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable successes in third-party food delivery operations in the digital platform era

Abstract: In the digital era, third-party food delivery operations are very popular all around the world. However, to achieve a sustainable operation for food delivery businesses is a challenging issue. Motivated by the fact that there is a lack of consolidated view towards the topic in the literature, we conduct a systematic literature review to identify how to achieve a sustainable operation for third-party food delivery and highlight the recent advances in this important area with the discussion of real-world practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 91 publications
0
0
0
Order By: Relevance
“…Consumers' good perceptions of halal products or Islamic services will arouse their intentions and decisions to use them. Knowing consumer perception of certain products and services, marketers can predict their decisions or actual behaviors in the future (Aisyah & Silvia, 2023;Chan et al, 2023;Li et al, 2022;Mishbakhudin & Aisyah, 2021;Rizki et al, 2021;Shaheen, 2016;Suhartanto et al, 2022;Thusi & Maduku, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumers' good perceptions of halal products or Islamic services will arouse their intentions and decisions to use them. Knowing consumer perception of certain products and services, marketers can predict their decisions or actual behaviors in the future (Aisyah & Silvia, 2023;Chan et al, 2023;Li et al, 2022;Mishbakhudin & Aisyah, 2021;Rizki et al, 2021;Shaheen, 2016;Suhartanto et al, 2022;Thusi & Maduku, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The other six indicators are no riba, viable alternative, social & welfare, innovative, and service quality, derived from Islamic Banking Bulletin (2013) and Shah et al (2016). Marketers can predict customers decisions or actual behaviors in the future based on their perception of a certain product or service (Aisyah & Silvia, 2023;Chan et al, 2023;Li et al, 2022;Mishbakhudin & Aisyah, 2021;Rizki et al, 2021;Shaheen, 2016;Suhartanto et al, 2022;Thusi & Maduku, 2020). This study used the five stages of the purchase decision process to measure consumers' decision to shop at Lazada Amanah's online Halal marketplace, which begins with identifying the problem, searching for necessary information, evaluating the available alternatives, deciding the best possible option, and ending with post-purchase evaluation (Cakici & Tekeli, 2022;Gulati, 2022Gulati, , 2023Kotler & Keller, 2016;Schiffman & Kanuk, 2007).…”
Section: Etikonomimentioning
confidence: 99%
“…This finding reflects varying perspectives on the benefits, challenges, and implications of engaging with external delivery partners, highlighting the need for further investigation into the underlying factors influencing this innovation adoption. Research on restaurant-delivery service collaboration during pandemics suggests that such partnerships can be beneficial, especially when demand is high and delivery distances are long (Chan, Cheung, Choi and Sheu, 2023). The spatial distribution of delivery areas, as well as service quality, influence the success of these collaborations (Feizizadeh, Adabikhosh and Panahi, 2023).…”
Section: Collaboration With Delivery Servicesmentioning
confidence: 99%
“…Most of the prior research of OFD focused on adopting various algorithms to enhance efficiency [3][4][5], devising pricing policies aimed at improving the profits and welfare of the platform [6], altering restaurant and menu option positions [7], or exploring the profiles of young customers [8]. Chan et al conducted a systematic literature review and identified five future areas, including technologies, behaviors and decisions of the restaurants, risk management, TBL, and post-coronavirus pandemic [9]. However, there is limited relevant research concerning customer switching behavior and loyalty.…”
Section: Introductionmentioning
confidence: 99%